Factors Affecting Profitability of Construction Company Sub-Sector - Halian, Wahana; Sinaga, Bonar M.; Novianti, Tanti (Indonesian Journal of Business and Entrepreneurship, 2020)
The increase is in construction activities is not always good considering that in the construction sub-sectors, the company is a long-term investment, and the payment is following the terms of project completion, causing a decrease in the company’s profitability. This study aims to analyze the company’s profitability in the construction subsector and the impact of the company’s external and internal factors in the construction subsector. This study uses a simulation method with a simultaneous equation model consisting of seven simultaneous equations and six identity equations estimated using the 2SLS method (Two-Stage Least Squares). The Results Showed that if the gross domestic product fell by 4% and the cost of revenue decreased by 5%, it resulted in an increase in return on assets by 12.95% (to 1.93% ROA) and returned on equity equal to 4. 07 (ROE to 27.96%). If inflation rises by 4% and the cost of revenue decreased by 5%, it would increase is the return on assets by 12.79 (ROA to 1.92%) and return on equity by 3:52% (ROE to 27.81%). If inflation rises by 4%, the gross domestic product falls by 4%, and cost of goods costs fall by 5%, the resulting in an increase in return on assets by 9.61% (ROA to 1.87%) and return on equity by 1.96% (ROE to 27.39%). Keywords: building construction subsector, external and internal factors, return on assets, return on equity, profitability, 2SLS